KUALITAS PELAYANAN KESEHATAN RAWAT JALAN DI RSUD dr. SOEHADI PRIJONEGORO KABUPATEN SRAGEN - - Sudaryanto (Master of Public Administration, Universitas Slamet Riyadi, 2016)
Hospital is a means for providing health service in order to increase the degree ofcommunity health which is needed by all community layers. That is why hospital isdemanded should be able to increase its service quality. This research wasintended to analyse the quality of service provided by the hospital studied fromselected five indicators. is health service user. Patient entitles to have primeservice which accords to the main objective of public service itself. Descriptivequalitative research type was used in this study. Respondents were selected on thebasis of accidental sampling. The respondents were selected without list ofpopulation; the respondets migh be medical doctor, nurse, clerical, or patient.Interview and document study were used for collecting the needed data. Interactiveanalysis model consisting of three elements i.e. data reduction, data display, andverification and conclusion drawing was used to analyse the data. Research findingindicated that quality of health care service for nonhospitalized patient treatment indr. Soehadi Prijonegoro Regional General Hospital in Sragen Regency according tofive selected indicators using in this study had already met the need and patient’expectation. Of five selected indicators had been able to fullfilled patient’ need.Five indicators needed by the patient mentioned include: building, means of healthservices, supporting medical kits, sufficient employees, dependability and ability inserving the patient, certainty of health service, administrative certainty in healthservice, fast respondability in serving patient’ need, hospitality and politeness,health service guarantee and administrative service, empathetic understanding,and heartly in serving. All of these gave trust to patient to have further treatment inRegional General Hospital of dr.Soehadi Prijonegoro.Key words: Quality of health service; health care; nonhospitalized patient treatment;